Identifying the airport as a key urban VOC source in the Pearl River Delta, China. (15th May 2023) - Zhu, Bo; Cao, Li-Ming; Xia, Shi-Yong; Niu, Ying-Bo; Man, Han-Yang; Du, Ke; Yu, Kuangyou; Huang, Xiao-Feng
Abstract: Volatile organic compounds (VOCs) are the main precursors of ozone (O3 ) and secondary organic aerosol (SOA) formation in the atmosphere. The traditional positive matrix factorization (PMF) source apportionment method is mainly based on the time series of VOCs at a single site, and its results cannot indicate the difference spatially. In this study, a refined spatial distribution study was carried out in Shenzhen in the Pearl River Delta (PRD) region, China, with 110 sampling sites covering the city. Ninety-two VOC compounds were quantitatively analyzed and the spatial distribution characteristics of various VOCs were obtained. Based on the PMF source apportionment of multisite samples, five types of sources and their spatial distributions of vehicle exhaust, gasoline leakage, industrial processes, airport-related sources and regional transport were identified. The airport source was resolved for the first time in the VOC source apportionment and was further verified by the measured source spectra in the airport. It is found that the airport-related sources accounted for 19% of the ambient VOC concentrations in Shenzhen and had strong Cl radical reaction activity, indicating that the airport-related sources may have a greater impact on O3 and SOA formation in coastal cities than previously expected. Graphical abstract: Image 1 Highlights: VOC samples were collected simultaneously at 110 sites in Shenzhen. Five VOC sources and their spatial distributions were identified by PMF. Airport-related sources were found to account for 19% of VOC concentrations. Airport-related sources may have great impact on O3 and SOA formation in PRD.